Agricultural practices to improve soil carbon sequestration in rice paddy soils - Ji Song, Hyeon (Burleigh Dodds Series in Agricultural Science, 2023)
Paddy rice systems are characterized by waterlogged conditions with high potential for CH4 emissions and soil organic carbon (SOC) sequestration. Therefore, it is necessary to evaluate the net global warming potential (GWP) of soil management considering SOC stock changes, and CH4 and N2O fluxes. Green manure application and straw retention slightly enhanced SOC stock, but highly increased net GWP due to high CH4 emissions. Aerobic pre-digestion of organic matter amended soils and water drainage during cropping are practices which significantly decrease net GWP. Moreover, silicate fertilizers with electron acceptors like oxidized iron and manganese also decrease net GWP. Biochar rather than compost as a stable organic amendment significantly increases SOC while decreasing net GWP. In conclusion, the combined management of organic amendments, aerobic pre-digestion, water drainage, and fertilizers could be a promising way to mitigate greenhouse gas emissions and favor C sequestration in rice paddies.